Development of a sports specific aerobic capacity test for Karate - A pilot study - Nunan, D. (Journal of Sports Science & Medicine, 2006)
The purpose of the study was to develop an aerobic fitness assessment test for competitive Karate practitioners and describe the preliminary findings. Five well-trained, competitive Karate practitioners participated in this study. A protocol simulating common attack strikes used in competition Karate sparring was developed from video analysis. In addition, pilot testing established a specific sequence of strikes and timings to be used in the test. The time to perform the strike sequence remained the same, whilst the time between strike sequence performances was progressively reduced. The aim of the test was to increase intensity of exercise through a decrease in recovery. On two separate occasions, absolute and relative peak oxygen uptake (VO2peak), peak ventilation (VEpeak), maximum heart rate (HRM), and time to exhaustion (TE) obtained during the test were recorded. Subjective feedback provided by the participants was positive in that participants felt the test accurately simulated actions of a competitive sparring situation, and as a result athletes felt more motivated to perform well on this test. There was no significant between test difference in absolute VO2peak, relative VO2peak, HRM and TE (p > 0.05), indicating a potentially high reproducibility with the new test for these variables (test 1-test 2 difference of 0.04 L·min-1, 1 ml·kg-1·min-1, -3 beats·min-1, and 28 s; respectively). However, VEpeak displayed potentially less reproducibility due to a significant difference observed between tests (test 1- test 2 difference of -2.8 L·min-1, p < 0.05). There was a significant relationship between TE and relative VO2peak (R2 = 0.77, p < 0.001). Further developments to the test will need to address issues with work rate/force output assessment/monitoring. The new test accurately simulates the actions of competitive Karate sparring.